2016
DOI: 10.1002/chin.201618100
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Sexterrylenetetracarboxylic Bisimides: NIR Dyes.

Abstract: Bisamide (I) is prepared by Suzuki cross‐coupling and subsequent oxidative ring closure reactions of the perylene units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was suggested that many polymer like glass fibers, carbon fibers, aramid fibres, basalt fibres, thermoplastic, thermosetting, polyester resin, epoxy resign and vinyl ester resign. Langhals et al, (2014) identified technical polymers by means of their remarkably strong auto fluorescence. The time constants of this fluorescence proved to be characteristic for the individual polymers and could be economically determined by integrating procedures.…”
Section: Issn: 2319-7706 Volume 7 Number 10 (2018)mentioning
confidence: 99%
“…It was suggested that many polymer like glass fibers, carbon fibers, aramid fibres, basalt fibres, thermoplastic, thermosetting, polyester resin, epoxy resign and vinyl ester resign. Langhals et al, (2014) identified technical polymers by means of their remarkably strong auto fluorescence. The time constants of this fluorescence proved to be characteristic for the individual polymers and could be economically determined by integrating procedures.…”
Section: Issn: 2319-7706 Volume 7 Number 10 (2018)mentioning
confidence: 99%